Analyzing Common Errors in Wudu and Prayer Practices: Strategies for Improvement (A Case Study of Students at SDN 034 Muaro Tabun, VII Koto District) - Andre, Lesis; Chindy Oktavia, Rina; Lestari, Ika; Febriani, Dika; Sari, Vivi Andika; Ramadhani, Widya; Dina, Dina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze common mistakes in ablution and prayer practices and their improvement strategies at SD N 034 Muaro Tabun, VII Koto District. In the observation activities that have been carried out, it was found that many children still make common mistakes in ablution practices such as not washing their entire face. This study uses a qualitative method with 45 students, 5 teachers and 1 principal as participants. Data were collected through interviews, observations and documentation. The results of the study show that by using various learning strategies and methods that are appropriate to the child's age, children find it easier to understand the concept of ablution and prayer and their practices in everyday life. In addition, the use of ice breaking also greatly helps restore children's focus so that children do not feel bored/tired in receiving the material. In conclusion, as educators we must realize that each child's learning type is different, so we must provide innovation in the learning methods and strategies carried out in schools.